The Influence of Attitudes and Subjective Norms on the Purchase Intention of Halal-Certified Wardah Products (A Study of Muslim Female Students at Muhammadiyah University of Jember) - Salsabilla Hurul Aini; Siti Khayisatuzahro Nur; Miftahul Hasanah (Yayasan Rahmat Islamiyah, 2026)
The development of the halal cosmetics industry in Indonesia shows changes in consumer behavior that increasingly consider aspects of quality, safety, and product suitability with religious values. Wardah as a pioneer of national halal cosmetics has become one of the brands widely used by Muslim consumers, especially female students. This study aims to analyze the influence of attitudes and subjective norms on the purchase intention of Wardah products among Muslim female students at the University of Muhammadiyah Jember. The study used a quantitative approach with a survey method of 322 respondents. Data collection was conducted through questionnaires and analyzed using multiple linear regression. The results showed that attitudes have a positive and significant effect on purchase intention (t = 11.511; sig. = 0.000). Subjective norms also have a positive and significant effect on purchase intention (t = 7.841; sig. = 0.000). Simultaneously, both variables have a significant effect on purchase intention (F = 149.926; sig. = 0.000) with a coefficient of determination of 0.481. The research findings show that individual evaluation of the product and social environmental support play an important role in shaping the purchase intention of halal cosmetics. This study strengthens the application of the Theory of Planned Behavior in explaining Muslim consumer behavior in the halal cosmetics industry.